1975
DOI: 10.1136/bmj.3.5977.195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of new beta-adrenergic blocking agent, Atenolol (Tenormin), on pain frequency, trinitrin consumption, and exercise ability.

Abstract: In 11 patients with severe angina pectoris a newblocking drug, atenolol (Tenormin; I.C.I. 66082), was found in a double-blind randomized trial to reduce significantly the frequencyofanginal attacks (P <0 001) and the amount of trinitrin consumed (P <0 03) in comparison with practolol and placebo. There was no significant improvement in the patients' ability to exercise on thebicycleergometer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Theoretically these properties should make atenolol a suitable P-blocker in the treatment of angina pectoris, as indicated in an earlier report on hypertensive patients (3). However, we have found only one paper on the effect of atenolol in long-term treatment of angina (8). In this study atenolol caused a highly significant drop in resting heart rate, exercise heart rate, exercise BP and hence pulse rate/BP product in all patients tested.…”
Section: Discussionmentioning
confidence: 53%
“…Theoretically these properties should make atenolol a suitable P-blocker in the treatment of angina pectoris, as indicated in an earlier report on hypertensive patients (3). However, we have found only one paper on the effect of atenolol in long-term treatment of angina (8). In this study atenolol caused a highly significant drop in resting heart rate, exercise heart rate, exercise BP and hence pulse rate/BP product in all patients tested.…”
Section: Discussionmentioning
confidence: 53%
“…Exercise tests were carried out in the sitting position on either the Elema-Schonander or Monark exercise bicycles (Roy, Day, and Sowton, 1975).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, while beta blockade withdrawal increases the basal heart rate, the rate at which ischaemia develops is reset at a higher level; hence, in some patients atenolol withdrawal produced no deterioration, just as in some patients beta block-281 ade produces no objective benefit. [28][29][30] A second mechanism proposed for withdrawal phenomena is rebound hypersensitivity of cardiac beta receptors to circulating catecholamines.' [1][2][3][4][5][6][7][8][9][10][11][12][13] While hypersensitivity to infused isoprenaline has been seen after propranolol withdrawal in hypertensive'2 and normal" subjects other studies have not confirmed this phenomenon.3132 At the time when rebound hypersensitivity is said to be present after atenolol withdrawall4 no acceleration of the heart rate response with exercise was seen in our patients in group 1 when compared with group 2.…”
Section: Symptomatic Changes (Group 1)mentioning
confidence: 99%